Paper engineers and mechanical devices of movable books of the 19th and 20th centuries - Mara Sarlatto (JLIS.it, 2016)
The article examines the evolution of pop-up children books in the period from the late eighteenth century and the end of the twentieth century and, in particular, the artistic personality of some publishers/paper engineer (Dean and Son, Lothar Meggendorfer, Ernest Nister, St. Louise Giraud, Vojtech Kubăsta ). The contribution also illustrates operation of some devices. It remains deliberately excluded from the survey the digital pop-up book, which has different characteristics and problems compared to the printed book.